2020
DOI: 10.1101/2020.04.25.20079640
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Outcomes in Saudi Arabia and the UK: A Tale of Two Kingdoms

Abstract: Background:While the number of COVID-19 cases and deaths around the world is starting to peak, it is essential to point out how different countries manage the outbreak and how different measures and experience resulted in different outcomes. This study aimed to compare the effect of the measures taken by Saudi Arabia and the United Kingdom (UK) governments on the outcome of the COVID-19 pandemic as predicted by a mathematical model. Method:Data on the numbers of cases, deaths and government measures were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 21 publications
0
27
1
Order By: Relevance
“…Aletreby et al [ 22 ] predicted that the pandemic would peak by the end of July 2020. Further, the work in [ 23 ] used the SIR model to predict future trends and compare the impact of control measures taken by Saudi Arabia and the United Kingdom on the outcomes of COVID-19 pandemic. Their results indicated that early extreme measures imposed by the Saudi authority played a major role in reducing the spread of the disease, compared to the UK.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Aletreby et al [ 22 ] predicted that the pandemic would peak by the end of July 2020. Further, the work in [ 23 ] used the SIR model to predict future trends and compare the impact of control measures taken by Saudi Arabia and the United Kingdom on the outcomes of COVID-19 pandemic. Their results indicated that early extreme measures imposed by the Saudi authority played a major role in reducing the spread of the disease, compared to the UK.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Absolute Percentage Error (MAPE) and coefficient of determination (R 2 ). Equations 5, (6) and 7were used to calculate the RMSE, MAE and MAPE respectively (10).…”
Section: Model Evaluationmentioning
confidence: 99%
“…Different mathematical models were used to estimate the COVID -19 dynamics in the literature depending on the stage of the epidemics. Exponential Logistic growth model was utilized to study the pattern of COVID-19 epidemics in early stages in KSA (6). It has also been utilized to model late COVID-19 stages in China (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Saudi Arabia, the number of COVID-19 cases has been increasing since February 2020. The Saudi Ministry of Health has made enormous efforts and guidelines to eradicate the virus [9], and the government established speci c lockdown precautions policies in March 2020: forcing individuals to quarantine themselves at home, suspending travel, imposing social distancing rules, and banning attendance at workplaces, schools, restaurants, shops, and gyms [9,10]. To date, Saudi Arabia has had around 268,934 con rmed cases and 2,760 deaths, which constitutes about 0.7% of the total population [11].…”
Section: Introductionmentioning
confidence: 99%